Editorial. (December 2015) - Barrett, Steve
Abstract : AFC Energy is making excellent progress in developing its alkaline fuel cell technology for industrial-scale applications, and will shortly have a demonstration system operational in Stade, Germany as part of the EU-funded Power-Up project.